The rapid deglaciation of the Skagafjörður fjord, northern Iceland. (16th August 2018) - Andrés, Nuria; Palacios, David; Sæmundsson, Þorsteinn; Brynjólfsson, Skafti; Fernández‐Fernández, José M.
Abstract : The Skagafjörður fjord in northern Iceland is located between the Tröllaskagi Peninsula in the east and the Skagi Peninsula in the west. The tributary valleys of the fjord originate in the highland area about 15 km north of the Hofsjökull icecap. The results of this work improve the knowledge of the deglaciation pattern in Skagafjörður and explore the adequacy of the 36 Cl cosmic ray exposure dating method in an Icelandic environment, where this method has rarely been applied to deglaciated surfaces. The 36 Cl dating method was applied to 13 rock samples taken on a transect from the coastal areas towards the highlands. All samples were obtained from rock outcrops with glacier‐polished surfaces from the Last Glaciation and from one of the few well‐preserved erratic boulders. The cosmogenic results, combined with previous radiocarbon results, indicate that the ice margin was situated in the outermost sector of Skagafjörður at approximately 17–15 ka BP. Subsequently, it retreated and occupied the central part of the fjord between 15 and 12 ka BP and then the innermost sector of the fjord about 11 ka BP. The samples collected between this position and the highlands show an average age of approximately 11 ka, indicating rapid deglaciation after the early Preboreal. These results agree with earlier studies of the deglaciation history of northern Iceland, reinforce previous deglaciation models in the area and enable a better understanding of glacial evolution in the North Atlantic from the Late Pleistocene to Holocene transition.